A Critique Of The Concept Of Growth In Secular Economics According To Syed Muhammad Naquib Al-Attas - Johnderose, Ahmad Qolbi Zidan; Hamijar, Muhammad Fajar; Nuha, Dzatu Aliviatin (PT. Student Rihlah Indonesia, 2025)
This research highlights the urgency of reformulating the concept of economic growth in secular economic thinking that contributes to the crisis of morality, justice and sustainability. This paradigm measures growth only quantitatively such as through GDP, but ignores the spiritual, ethical or moral, and social dimensions. This research aims to examine Syed Muhammad Naquib al-Attas' critique of the paradigm and offer an alternative framework based on the Islamic worldview. The method used in this research is qualitative literature with content analysis of al-Attas' main works and related academic literature. The results show that al-Attas sees the epistemological crisis of secular economics as stemming from the separation between science and revelation. He offers a solution in the form of economic Islamisation through the integration of the values of tawhid, adab, and maqashid al-syari'ah. The novelty of this research lies in the philosophical synthesis between al-Attas' metaphysical thinking and contemporary economic challenges, and encourages a shift in economic policy from material accumulation to an ethical and spiritual approach, especially in Muslim countries that want more holistic development.